Exploring Gender Equity in Ecological Restoration: The Case of a Market-Based Program in Kenya - Kariuki, J.; Birner, Regina (University of Wisconsin Press, 2021)
Payments for Ecosystem Services (PES) provide incentives to landowners to manage resources in ways that deliver ecosystem services, such as through restoration activities. Under a proliferation of initiatives to restore degraded lands, innovative institutional arrangements that promote ecological restoration are emerging. However, exclusion of the human factor is considered a limitation of restoration theory and practice, and recognition of men’s and women’s roles in restoring landscapes is largely neglected. As the United Nations Decade on Ecosystem Restoration commences, this study uses PES as an entry point to explore gender equity in restoration projects. Focused on the Mara North Conservancy in Kenya, the study presents a framework for which qualitative approaches including Process Net-map and intra-household interviews are applied to uncover drivers and constraints associated with processes of gender exclusion and inclusion. The results reveal that 1) power imbalances condition socio-economic outcomes of PES schemes by reinforcing historical inequities in land tenure, and that 2) governance structures exclude women from decision-making processes and from receiving direct PES benefits despite their labor contributions to restoration activities; while men incur financial costs that are not adequately accounted for under direct payments. The study demonstrates the potential to apply new methodologies and define indicators that enable the identification of complex social dimensions in ecological restoration. Critical reflection on whether the neglect of social aspects restrict the potential for ecological restoration to address the very same inequities that contribute to degradation of threatened landscapes is encouraged.